Severe thermal injury of larynx in a child following accidental ingestion of hot tea - Jamir, Bendangienla; S. P., Senthil Kumar; Azam, Md Nawed; Kumar, Arun; Patnayak, Pupun (International Journal of Contemporary Pediatrics, 2019)
Thermal injury to the upper respiratory tract caused by aspiration of hot liquids resulting in laryngeal edema and subsequent obstruction of the airway is commonly not seen in the pediatric population. Unlike adults, children are more prone for subglottic injury, swelling and resulting obstruction of the airway due to the smaller size of the trachea and relatively large epiglottis. Examination of the airway with laryngoscopy hence should be recommended in all patients with inhalational and aspiration burn injury as it will help in guiding airway management and preventing development of complications. Authors report a case of a 3-year-old male child with accidental ingestion of just made hot tea. Upon presentation there was severe stridor and signs of respiratory distress requiring emergency intubation. Direct laryngoscopy revealed glottic edema and ulcer. Upper GI endoscopy showed erythematous arytenoids, esophagus and stomach showing few erythematous flat lesions. Chest radiographic examination showed bilateral para cardiac and perihilar inhomogeneous opacities suggestive of aspiration pneumonitis. The child was gradually weaned and extubated on day three of admission. Ingestion of hot liquids can cause airway and esophageal thermal burns. Rapid diagnosis and treatment are essential in management of inhalational and aspiration burn injury to reduce the morbidity, mortality and long-term sequelae in these patients. Children are more prone for burn accidents due to their curious and exploratory behavior and their inability to perceive the hazards. Since most of the pediatric burn accidents happen at home, parents should be offered education about prevention of burn and advised on how to manage and treat minor burn injuries and to watch for any warning signs in which case to rush to the nearest hospital.